Pengaruh Perendaman Campuran Larutan Nira Tebu Dan Asam Sitrat Untuk Memperpanjang Vase Life Bunga Mawar (Rosa hybrida) Potong - Raharja, I Nyoman Dharma Putra; Mahendra, Made Sudiana; Sugiarta, Anak Agung Gede (Nandur, 2023)
Roses have the potential to be developed in Indonesia but the freshness of cut roses quickly decreases after postharvest. The research was conducted in January to March 2023 at the Ecophysiology Laboratory, Faculty of Agriculture, Udayana University. This study aims to determine the effect of soaking with a mixture of sugarcane juice and citric acid solution to maintain the vase life of cut roses. The research design used a completely randomized design (CRD) with 2 factors. The first factor was sugarcane juice consisting of 4 treatments: 0ml, 10ml, 20ml and 30ml. The second factor, namely citric acid, consisted of 4 treatments: 0ppm, 50ppm, 100ppm and 150ppm. The treatment was repeated 2 times to obtain 32 experimental units. The results showed an interaction between the sugarcane juice and citric acid treatment on the variable changes in flower diameter, acidity of the solution, and flower vase life. As a single factor, sugarcane juice has a significant effect on the variables of flower diameter, absorbed solution, solution pH, and flower vase life. As a single factor, citric acid has a significant effect on the variable diameter of the flower, the absorbed solution, the pH of the solution, and the vase life of the flower. A mixture of sugarcane juice and citric acid at 10ml and 150ppm maintained the appearance of cut roses for up to 7 days.